Памятник книжной культуры староверов Даугавпилсского р-на - Михеев, Григорий (Slavistica Vilnensis, 2011)
Grigory MiheevThe Historical Book of russian Old Believers found in the Daugavpils RegionThis article presens the description of the old print book of Russian Old Believers found and researched in Daugavpils, Latvia in 2010. This old print of the Book of Psalmes, with some handwritten inscriptions presents an unfinished work of an unknown scribe and restorator of incunable Books of Psalms. The description contains as following: the condition of the book binding and features of preserved part of printed texts, paper and 8 types of watermarks that were found on it. The pictures of filigrees and short details about paper mills, where the similar filigrees were used, are attached. The author provides the reproduction of the font, miniature, colophon, initials, three of publications and two hand written records. The print is identified as being close or similar to the Books of Psalmes and the other books printed by Pyotr Mstislavets, Vasil Garaburda and Mamonichi in the years between 1574 and 1601. The finding has been defined as similar to the “Black Dot Book of Psalms”, presumably printed by Mamnochis printing house in Vilnus. Its closest copy might be considered “The Red Dot Book of Psalmes” printed by Pyotr Mstislavets in 1678 in the same printing house. The date of the described print has been estimated as not later than July, 1600.